Benchmark: Evaluating our emotional connection to sport & sponsors. True North Research Report October 2020 (True North Research, 2020)
The latest BenchMark Report from True North Research has shown how COVID-19 has negatively affected Australia`s overall engagement with sport, lowering familiarity, the size of supporter bases, and emotional connection.